Effect of cryogenic and ambient crushed rubber on the mechanical properties of hot mixes asphalts - Neto, Silvrano Adonias Dantas (2009)
The crumb rubber used to produce asphalt rubber binders can be obtained either through the ambient grinding or the cryogenic processes. The final product obtained usually presents significant differences which influence the physical properties of asphalt rubber binders and, consequently, the mechanical properties of the asphalt rubber hot mixes produced with these modified binders. The objective of the study presented in this paper is to learn about the influence that the type of crumb rubber used to produce asphalt rubber binders has on the mechanical properties of dense graded asphalt hot mixes. Asphalt rubber binders were produced with a 21% of crumb rubber obtained through the ambient grinding and cryogenic processes. The dense graded asphalt hot mixes were produced with asphalt rubber and straight binders for comparison. The tests used to evaluate the mechanical properties were: a) tensile strength; b) fatigue life; c) resilient modulus and d) permanent deformation (RSST-CH,). The results show that the most significant difference in relation to the mechanical behavior of the asphalt rubber hot mixes tested was the resistance to permanent deformation which was enhanced by the use of crumb rubber obtained through the ambient grinding process.